Modelling and analysis of the UHVDC transmission receiving system considering 300 Mvar novel synchronous condenser. Issue 16 (8th January 2019) - Ma, Yiming; Ruan, Ling; Xiao, Yang; Zhou, Libing; Wang, Jin; Tao, Qian
Abstract : This study presents an analytical modelling method of the ultra‐high voltage direct current (UHVDC) receiving system including converter station, AC power grid, novel synchronous condenser, and wind turbine. A detailed model of UHVDC receiving converter station, considering the novel synchronous condenser system, is proposed. A simplified model of wind farm is established to consider the influence of renewable generation plant near to converter station. Based on the proposed model, the characteristics of novel synchronous condenser is studied in different dynamic condition of power grid, like AC voltage drop and DC bipolar blocking. A numerical simulation model by Simulink ® is applied to validate the presented analytical model.